2003
DOI: 10.1167/iovs.03-0077
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with the Incidence of Open-Angle Glaucoma: The Visual Impairment Project

Abstract: Certain nonmodifiable risk factors may be used to identify high-risk individuals, and increased IOP remains an important modifiable risk factor for OAG. However, more prospective studies on risk factors are required to clarify further the etiological picture of OAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
224
2
26

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(265 citation statements)
references
References 46 publications
13
224
2
26
Order By: Relevance
“…This result revealed the importance of further studies examining the CYP1A1m1 polymorphism and POAG. Le et al (2003) showed that POAG development was not related to gender, which agrees with the results of Rudnicka et al (2006). Cedrone et al (2008) observed a high prevalence of glaucoma in female patients, which was similar to a study conducted in Dalby, Sweden (Bengtsson, 1989).…”
Section: Discussionsupporting
confidence: 87%
“…This result revealed the importance of further studies examining the CYP1A1m1 polymorphism and POAG. Le et al (2003) showed that POAG development was not related to gender, which agrees with the results of Rudnicka et al (2006). Cedrone et al (2008) observed a high prevalence of glaucoma in female patients, which was similar to a study conducted in Dalby, Sweden (Bengtsson, 1989).…”
Section: Discussionsupporting
confidence: 87%
“…1 Some previous studies have concluded that family histories of glaucoma, severe myopia, or high IOP constitute major risk factors. 2 Of these identified risk factors, IOP has received attention for many years as a potential modifiable risk factor. [3][4][5] Although the mechanism underlying IOP elevation are not fully understood, a recent study reported associations between systemic health parameters, such as, hypertension, diabetes, and obesity indexes (eg, waist circumference and BMI) and IOP elevation.…”
Section: Introductionmentioning
confidence: 99%
“…1 The well-known risk factors for glaucoma include African ethnicity, family history of glaucoma, severe myopia, and high intraocular pressure (IOP). 1,2 Of these risk factors, high IOP is one of the strongest risk factors for glaucoma, and therefore, reducing IOP may delay the development of primary open-angle glaucoma. 3,4 Metabolic syndrome (MetS) is a collection of risk factors that increases the chance of an individual developing cardiovascular disease and diabetes mellitus (DM).…”
Section: Introductionmentioning
confidence: 99%